TIMP1 Is A Potential Key Gene Associated With The Pathogenesis And Prognosis Of Ulcerative Colitis-Associated Colorectal Cancer - Huang R (OncoTargets and Therapy, 2019)
Ru Huang,1,* Kaijing Wang,2,* Lei Gao,1 Wei Gao2 1Department of Heart Failure, Research Center for Translational Medicine, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 2Department of Colorectal Surgery, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei GaoDepartment of Colorectal Surgery, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaEmail yoursgaowei@163.comLei GaoDepartment of Heart Failure, Research Center for Translational Medicine, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of ChinaEmail gldlykdx@163.comPurpose: Colorectal cancer (CRC) is the third most frequently diagnosed cancer worldwide. As a high-risk factor for CRC, ulcerative colitis (UC) has been demonstrated to lead to epithelial dysplasia, DNA damage, and eventually cancer. There are approximately 18% of patients with UC may develop CRC.Patients and methods: The gene expression profiles were retrieved from the Gene Expression Omnibus. The Database for Annotation, Visualization and Integrated Discovery was employed to conduct gene annotations. Protein-protein interaction network was constructed by the Search Tool for the Retrieval of Interacting Genes, and further analysed by the Molecular Complex Detection. The correlation between TIMP1 and prognosis was evaluated by the Gene Expression Proﬁling Interactive Analysis. To predict the potential functions of TIMP1, the GeneMANIA, Coremine, and FunRich were employed. After transfection with small interfering RNA targeting TIMP1, cell proliferation, migration, and apoptosis were determined by CCK-8, scratch wound, and Annexin V-FITC/PI assays, respectively.Results: TIMP1, consistently overexpressed in the initiation and progression of UC-associated CRC (ucaCRC), was identified to be a potential biomarker for the prognosis of patients with CRC. Experimental results showed knockdown of TIMP1 could increase the migration, while did not affect the proliferation and apoptosis of RKO cells. The role of TIMP1 in the malignant transformation of ucaCRC was confirmed by using the protein/gene interactions and biological process annotation and validated by analysing the transcription factors targeting TIMP1.Conclusion: TIMP1 is consistently upregulated in the pathological process of ucaCRC and can be a potential biomarker for the worse prognosis of CRC.Keywords: colitis ulcerative, colorectal neoplasms, high-throughput screening assays, prognosis